2018
DOI: 10.1097/md.0000000000010225
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for chronic pelvic inflammatory disease

Abstract: Background:Chronic pelvic inflammation disease (PID) is a difficult-to-treat gynecological disorder with complex etiologies. Acupuncture has been applied widely for treating chronic pelvic inflammation or chronic pelvic pain symptoms in China. The aim of this review is to undertake a systematic review to estimate the effectiveness and safety of acupuncture on chronic PID.Methods:A literature search will be conducted electronically with date up to October 2018 in MEDLINE, Cochrane Library, EBASE, and CNKI datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It is necessary to introduce EBM into the field of traditional Chinese medicine (TCM) characterized by syndrome differentiation and treatment if we want to make TCM from individual to group. 6 , 7 Acupuncture, as one of the important disciplines in TCM, is a simple, efficient, economical, and safe means for treating pain syndromes, 8–11 chronic inflammatory disorders, 12 , 13 and other indications and has become a major part of international complementary and alternative medicine. 14 With the development of EBM, the quantity of literature on systematic review/meta-analysis and guidelines related to acupuncture therapy is increasing, which means that acupuncture is becoming a standardized and normal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to introduce EBM into the field of traditional Chinese medicine (TCM) characterized by syndrome differentiation and treatment if we want to make TCM from individual to group. 6 , 7 Acupuncture, as one of the important disciplines in TCM, is a simple, efficient, economical, and safe means for treating pain syndromes, 8–11 chronic inflammatory disorders, 12 , 13 and other indications and has become a major part of international complementary and alternative medicine. 14 With the development of EBM, the quantity of literature on systematic review/meta-analysis and guidelines related to acupuncture therapy is increasing, which means that acupuncture is becoming a standardized and normal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…As a traditional Chinese medicine treatment, acupuncture has been widely used in China for more than 3,000 years and plays an important role in the treatment of chronic diseases in contemporary medicine (Lee et al, 2008;Cheng et al, 2018). For the treatment of these chronic diseases, pain relief, and improvement of body function are two main application directions of acupuncture stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Later, when US President Nixon visited China in 1972, the accompanying journalists experienced acupuncture for analgesia, which made medical workers worldwide arouse great interest in acupuncture for treating diseases [ 74 , 75 ]. Acupuncture has a long history of treating gynecological diseases, and abundant studies have shown that acupuncture is beneficial, particularly in treating CPID [ 76 , 77 ]. There are many categories of acupuncture treating CPID, including filiform acupuncture, warming-acupuncture, etc.…”
Section: Researching the Overview Of Acupuncture And Moxibustion In Treating Pidmentioning
confidence: 99%